THE VOLATILITY OF WORLD CRUDE OIL PRICES - Haryo Kuncoro (Economic Journal of Emerging Markets, 2011)
The role of oil in an economy is very crucial. This article measures the world oil price uncer-tainty based on conditional standard deviations. It focuses on the volatility of crude oil price in United Kingdom, Texas, and Dubai markets, from January, 1980 to May, 2010. It finds the evidence that asymmetric leverage effects are not found. It also finds that volatility process in returns to its mean only evidenced in Dubai. These findings have some important implications for Indonesia. The government might use the dynamic of oil price in Dubai market as a benchmark to set up its state budget to realize fiscal sustainability.Keywords: Oil price, volatility, asymmetric leverage, fiscal sustainabilityJEL classification numbers: C22, Q43